URGENSI PORTOFOLIO DALAM PEMBELAJARAN - Rumhadi, Tri (Balai Diklat Keagamaan Surabaya, 2018)
In the process of learning often occurs delivery of teacher messages to students experiencing problems both in terms of students' understanding and in terms of student activeness. The main principle is the involvement of all or most of the students'self potential (physical and non physical) and meaningfulness for themselves and their life today and in the future (life skill). In addition, the assessment becomes a problem, especially inferring the value of students in competence skills. Required assessment model to facilitate students in understanding the material, therefore through the portfolio which is one of the teacher's efforts to reduce the dominance of teachers in learning which essentially draws the conclusions of competence skills appropriately. In the learning process that needs to be considered is how to design the portfolio by taking into account the characteristics of students. Portfolio evidence collected in the form of product, performance, or project tasks collected from the assessment by the students. All portfolio evidence collected from various aspects wil l be best taken to i nfer students' skills competencies.